Immunotherapy for B-Cell Lymphoma: Current Status and Prospective Advances - Hollander, Nurit (Frontiers in Immunology, 2012)
Therapy for non-Hodgkin's lymphoma has progressed significantly over the last decades. However, the majority of patients remain incurable, and novel therapies are needed. Because immunotherapy ideally offers target selectivity, an ever increasing number of immunotherapies, both passive and active, are undergoing development. The champion of passive immunotherapy to date is the anti-CD20 monoclonal antibody rituximab that revolutionized the standard of care for lymphoma. The great success of rituximab catalyzed the development of new passive immunotherapy strategies that are currently undergoing clinical evaluation. These include improvement of rituximab efficacy, newer generation anti-CD20 antibodies, drug-conjugated and radiolabelled anti-CD20 antibodies, monoclonal antibodies targeting non-CD20 lymphoma antigens, and bispecific antibodies. Active immunotherapy aims at inducing long-lasting antitumor immunity, thereby limiting the likelihood of relapse. Current clinical studies of active immunotherapy for lymphoma consist largely of vaccination and immune checkpoint blockade. A variety of protein- and cell-based vaccines are being tested in ongoing clinical studies. Recently completed phase III clinical trials of an idiotype protein vaccine suggest that the vaccine may have clinical activity in a subset of patients. Efforts to enhance the efficacy of active immunotherapy are ongoing with an emphasis on optimization of antigen delivery and presentation of vaccines and modulation of the immune system toward counteracting immunosuppression, using antibodies against immune regulatory checkpoints. This article discusses results of the various immunotherapy approaches applied to date for B-cell lymphoma and the ongoing trials to improve their effect.